The Martahi Tradition as a Social Practice of Mutual Assistance for the Mandailing Community in Bahap Village, North Sumatra - Ade Sakina Pane; Sakti Ritonga (JURNAL PENDIDIKAN IPS, 2025)
The Martahi tradition is a form of customary deliberation (musyawarah) that continues to be upheld by the people of Bahap Village. This tradition serves not only as a means of mutual cooperation in easing the financial burden of wedding ceremonies but also embodies strong values of kinship and social solidarity. This study employs a qualitative approach with descriptive methods. Data sources include both primary and secondary data, obtained through observation, interviews, and documentation. Data analysis uses the Miles and Huberman model, with data validation conducted through source triangulation, methodological triangulation, and member checking. The findings reveal that Martahi is a hereditary practice of communal deliberation that has become a social mechanism for strengthening social cohesion, fostering interpersonal relationships, and preserving local cultural values. This tradition not only reflects the spirit of mutual assistance but also aligns with Islamic principles such as ukhuwah (brotherhood), ta’awun (mutual assistance in goodness), and collective consultation (shura) in resolving community matters.